PENERAPAN MERIT SYSTEM BERDASARKAN KOMPETENSI PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SORONG: - , Otten Marsun Isir; Nurlinah; A.M Rusli; Nur Arkam (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This research aims to determine the implementation of a merit system based on employee competency at the Sorong City Investment and One Stop Integrated Services Service; employee competency which is influenced by the implementation of the merit system; obstacles to implementing the merit system in the Sorong City Government, especially the Investment and One-Stop Integrated Services Department. The method used is qualitative and descriptive analysis. Research data was obtained through observation and interviews. This research was conducted in Sorong City, Southwest Papua. The results of the research show that the implementation of a merit system based on employee competency in Sorong City, especially in the PMPTSP Service, has not fully run smoothly based on lack of resources, lack of support from superiors or city government, limited time and focus, no clear competency development plan and problems with resistance to change